2017
DOI: 10.1007/s40195-017-0642-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Microstructure and Residual Stress Between TIG and MAG Welding Using Low Transformation Temperature Welding Filler

Abstract: A Cr-Ni type of low transformation temperature (LTT) welding filler was devised in the present study. The LTT weld microstructures of the tungsten inert gas (TIG) and metal active gas (MAG) weldings were investigated by using electron-backscattered diffraction and orientation imaging microscopy. The results showed that the LTT weld microstructures prepared by TIG and MAG weldings were primarily martensite with 17.5% and 8.0% retained austenite, respectively. The LTT weld metal using TIG welding had larger grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Welding is one of the most practical techniques for assembling structures [1], such as ships, automobiles, and electronic goods [2]. For the effective design and analysis of the welding process, it is of great significance to accurately calculate the transient temperature field because the welding thermal cycles play a pivotal role in the prediction of the microstructure, residual stress, distortion, and their characteristics of welded joints [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Welding is one of the most practical techniques for assembling structures [1], such as ships, automobiles, and electronic goods [2]. For the effective design and analysis of the welding process, it is of great significance to accurately calculate the transient temperature field because the welding thermal cycles play a pivotal role in the prediction of the microstructure, residual stress, distortion, and their characteristics of welded joints [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to fatigue life improvement, the researchers also used the LTT alloys to reduce distortion [ 16 ] and to resist cold cracking [ 17 ]. In order to obtain an optimized residual stress around the weld zone, much attention was focused on the effects of the martensite start (Ms) temperature, which involved both experimental measurements and numerical simulation [ 18 , 19 , 20 ]. It was found that if the martensitic transformation occurred at an elevated temperature of more than 400 °C, the martensite finish (Mf) temperature would be located above the ambient temperature, resulting in a build-up tensile stress due to thermal contraction during the cooling process [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are some investigations [10][11][12][13][14][15][16][17][18][19] focus on microstructure and mechanical properties along the transition zone of DMWs, and lots of studies on LTT deposited metals covering from microstructure, residual stress [8], mechanical properties [1,7,9,20,21], cracking susceptibility [22], and distortion engineering [23]. The research studies related to the effects of chemical composition on solidification behaviour, microstructure, strain localisation, and dislocation density of welding transition zone on HSLA steels using LTT welding consumables are still limited.…”
Section: Introductionmentioning
confidence: 99%